Conditions regarding the application of the criminal law more favorable to the facts under trial - Anane, Ivan (Technium Social Sciences Journal, 2024)
If one or more criminal laws have intervened from the commission of the crime to the final judgment of the case, the most favorable law shall be applied. When the previous criminal law is more favorable, the complementary punishments that have a counterpart in the new criminal law are applied in the content and limits provided by it, and those that are no longer provided in the new criminal law are no longer applied. The Criminal Code regulates only the situation between the commission of the crime and the final judgment of the case. If a change in the conditions of incrimination or prosecution that would lead to impunity would occur after the final judgment was pronounced, during the execution of the sentence or after execution, when it still produces certain consequences, the respective convicts would not be able to benefit from the application of the criminal law under the legal basis. Understanding the criminal law in a broad sense, as a norm that includes not only the norms that provide for criminalization and punishment, but all kinds of criminal norms, as well as those extra-criminal norms that the criminal law refers to and which have an impact on incrimination, criminal liability or punishment in the sense that they can remove, aggravate or mitigate them. To be justiciable does not only mean to answer before the court for the committed act, but also to benefit from a more favorable criminal law, so that a balance is established between criminal liability and the need to reintegrate into society a suspect/defendant/convict for the smooth running of an open society.